Studi Prediktif Dampak Dukungan Jokowi Sebagai Outgoing President Terhadap Peluang Kemenangan Kandidat Presiden Yang Didukungnya Pada Pilpres 2024: Pola kasus: Obama, Vazquez, Uribe, SBY, Bachelet, Lula, dan Duterte - Amri Hakim; Zamhasari (JOELS: Journal of Election and Leadership, 2023)
This paper aims to find the impact of outgoing president support to the winning probability of its endorsed candidate in presidential election, and predicts the winning probability of Jokowi’s endorsed candidate in Indonesia 2024 presidential election. By generalizing Obama, Vazquez, Uribe, SBY, Bachelet, Lula, and Duterte’s cases it is found that president candidates who endorsed by outgoing presidents with at least 50% public approval have 71% chance to winning the presidential election and 29% chance to lose, and with the public approval over 85% the probability is increase to 100%. The endorsed candidates who wins the election mostly were the minister of outgoing president whose contribute to the high approval ratings. Meanwhile, in the case of lost candidates the unfirm support from outgoing presiden and the candidate who already had been president with 28% approval ratings found as the causes. Through this generalization it is predicted that if Jokowi able to maintain his public approval rating at least 50%, and endorse one of his success ministers whom also come from the same party then in the 2024 Indonesia’s president election this candidate possibly will be the winner with 71% chance, also if his approval ratings reaching out over 85% the chance will be 100%.